Factors affecting the improvement of visual acuity after cataract surgery among cataract patients in Malaysia based on the national eye database 2014-2018 - Sa'at, Nadiah (2021)
Introduction: Blindness and visual impairment are part of a global burden of eyes disease. Cataract is one of leading causes of blindness. Objective: To determine the proportion and factors associated with visual acuity (VA) improvement among cataract patients after surgery in Malaysia using data from the National Eye Database. Method: This was a retrospective cohort study using data from National Eye Database (NED). Cataract patients who underwent surgery and were registered from January 2014 to December 2018 with age over 18 years old were extracted from database. Patients’ sociodemographic, comorbidities, surgical factors, and related complication factors were extracted from the database. The outcome was measure from pre-and postoperative VA differences and categorised as improve, no change, and worse. Differences proportion in VA between before and after surgery were analysed using the Stuart-Maxwell Marginal Homogeneity test. Ordinal logistic regression was used to identify the association between the factors and the outcome. Result presentation using odds ratio and 95% confidence interval (CI). Results: A total of 199,826 patients with a mean age of 66.5(9.57) years involved in this study and 96.2% achieved improvement VA after undergoing cataract surgery. Results from marginal homogeneity test on VA before and after surgery had significant differences (p <0.001). There were 80.9% VA change from borderline to good and poor to borderline and good. Multivariable analysis showed improvement of VA was significantly higher in patients with age group 41-60 years old (OR: 1.15; 95% CI: 1.03, 1.29), female patients (OR: 1.07; 95% CI: 1.02, 1.13), Malay groups (OR: 1.63; 95% CI: 1.54, 1.73) and senile cause of cataract (OR: 1.39; 95% CI: 1.12, 1.73). The likelihood of improvement VA in the absence of ocular comorbidities (OR: 1.67; 95% CI: 1.58, 1.77), surgery using ECCE (OR: 1.98; 95% CI: 1.36, 2.86), presence of IOL (OR: 1.95; 95% CI: 1.67, 2.27), surgery of <30 minutes (OR: 1.42; 95% CI: 1.26, 1.61), and surgeries performed by a medical officer (OR: 1.47; 95% CI: 1.28, 1.68). Patients without intraoperative and postoperative complications had 1.21 (95% CI: 1.08,1.34) and 10.85 (95% CI: 10.24,11.51) times higher odds of improving VA. Conclusion: The percentage of improved VA after surgery among cataract patients in Malaysia was high. The findings from this study can guide the doctors, ophthalmologists, and researchers to identify the patients who have the associated factors that are highly likely to get improvement in VA after surgery.